The extreme Arctic ozone depletion in 2020 as was observed from Svalbard (EXAODEP-2020) - Petkov, Boyan H; Vitale, Vito; Di Carlo, Piero; Hansen, Georg H; Svendby, Tove M; Láska, Kamil; Sobolewski, Piotr S; Solomatnikova, Anna; Pavlova, Kseniya; Johnsen, Bjørn; Posyniak, Michal A; Elster, Josef; et al. (Zenodo, 2022)
This is chapter 4 of the State of Environmental Science in Svalbard (SESS) report 2021. Strong stratospheric ozone reductions during the spring months were first observed in Antarctica in the early 1980s. Follow-up ozone monitoring showed that such reductions occurred annually to a varying extent, mainly in the Southern Hemisphere. However, similar events were occasionally observed also in the Northern Hemisphere; these Arctic ozone reductions were especially pronounced in 1996, 1997, 2011 and 2020. Ozone distribution maps for March (Arctic spring) clearly show the strength of these episodes and how they contrast with the usual Arctic ozone behaviour. Comparison with the ozone distribution during the Antarctic spring (October) in the same years reveals that the extremely strong 2020 Arctic episode was comparable to the ozone depletion events in the Antarctic. According to current knowledge, these phenomena are triggered by the specific dynamics in the atmosphere over the polar regions in late winter and early spring when an extremely large vortex forms in the stratosphere and closes off a certain volume of the air from external impacts. That leads to a deep cooling and the formation of clouds in the low stratosphere. Heterogeneous chemical reactions taking place on the particles within these clouds form active chlorine species which destroy ozone. Usually, the Arctic polar vortex is much less intensive than the Antarctic one and is unable to create the conditions for a strong ozone reduction, which explains the differences between hemispheres. This report presents total ozone levels and solar ultraviolet (UV) radiation during the 2020 episode as measured from Svalbard. The stratospheric ozone reduction in spring 2020 nearly doubled the amount of UV-B radiation that reached the ground. This could significantly stress organisms adapted to a certain level of UV-B irradiance.